Left Atrial Enlargement and the Risk of Stroke: A Meta-Analysis of Prospective Cohort Studies - Xu, Yicheng; Zhao, Liming; Zhang, Lvming; Han, Yalei; Wang, Peifu; Yu, Shengyuan (Frontiers in Neurology, 2020)
Background The association between left atrial size and the risk of stroke has not been fully understood . We performed a meta-analysis of prospective cohort studies to determine whether left atrial enlargement (LAE) is associated with an increased risk of stroke. Methods We searched PubMed, EMBASE, Web of Science, and the Cochrane Library through May 2019. Prospective cohort studies were included if they reported hazard ratios (HRs) and corresponding 95% CIs of stroke with respect to LAE. All meta-analyses were performed using a random-effects model. Results Six studies involving 66,007 participants and 3549 stroke events were included. Compared with patients without LAE, those with LAE had an increased risk of stroke (adjusted HR 1.68; 95% CI 1.36-2.07). There was also a graded association with stroke relating to LAE (adjusted HR for mild LAE 1.50, 95% CI 0.98–2.28，moderate LAE 1.40, 95% CI 1.12–1.75, and severe LAE 1.59, 95% CI 1.33–1.90; respectively). Furthermore, for each increase of 1 cm in left atrial diameter, the odds of stroke were increased by 24% (adjusted HR 1.24; 95% CI 1.03-1.50). Conclusions Our meta-analysis demonstrated that LAE is associated with an increased and graded risk of stroke.